2022
DOI: 10.3390/agronomy12030715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Density and Row Spacing on the Yielding and Morphological Features of Pea (Pisum sativum L.)

Abstract: The aim of the study was to evaluate the effect of planting density and row spacing in pea on the plant growth, yield, structural seed yield components, and some plant indices in the central-and-northern part of Poland. Field experiments were performed in 2016–2019. The study involved a Polish pea cultivar, Batuta (semi-leafless). Three planting densities were applied (70, 90, and 110 seeds per 1 m2), with two row spacings (16 and 32 cm), in four replications on 20 m2 plots There was considerable pea sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The variety Simona was distinguished from the others with the highest protein content, the protein content was very similar for the variety Ieva DS, and the variety Respect significantly accumulated the lowest content of protein. This confirms previous findings in the literature that differences in climate, soil, varieties, and agronomic practices may cause a different yield and protein content [22,32,35]. We found that fertilizers did not have a significant influence on protein content.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The variety Simona was distinguished from the others with the highest protein content, the protein content was very similar for the variety Ieva DS, and the variety Respect significantly accumulated the lowest content of protein. This confirms previous findings in the literature that differences in climate, soil, varieties, and agronomic practices may cause a different yield and protein content [22,32,35]. We found that fertilizers did not have a significant influence on protein content.…”
Section: Discussionsupporting
confidence: 92%
“…In a study with eight pea cultivars, it was found that seed yield had a strong relationship with weather factors and the reproductive phase was limited by stress [ 31 ]. The most important factor that determined seed yield and protein content was the sum of the rainfall over the vegetation period [ 32 ]. Kuznetsov et al [ 30 ] established a moderate relationship (r = 0.486) between pea yield and the amount of precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the highest plant density per 1 m 2 (90 pods m −2 ) significantly reduced seed weight per plant compared to lower densities (75 and 60 pods m −2 ) by 13.5% and 9.5%, respectively. In studies by Borowska et al [23], Podleśny [26], and Prusi ński and Borowska [40], higher plant density reduced the number of pods per plant. However, Pospišil and Pospišil [41] found no significant effect of higher plant density on white lupin yield but showed that an increase in plant density above 60 plants per m 2 significantly reduced the number of pods, seeds per pod, and seed weight per plant.…”
Section: White Lupine Seed Yield and Its Componentsmentioning
confidence: 98%
“…However, Pospišil and Pospišil [41] found no significant effect of higher plant density on white lupin yield but showed that an increase in plant density above 60 plants per m 2 significantly reduced the number of pods, seeds per pod, and seed weight per plant. Prusi ński and Borkowska [40] indicated that the number of pods per plant and per 1 m 2 had the greatest impact on white lupin yield. Koetz et al [42] showed an increase in seed yield (18%) when the inter-row spacing was increased from 25 to 50 cm.…”
Section: White Lupine Seed Yield and Its Componentsmentioning
confidence: 99%
See 1 more Smart Citation